Using of Remote Sensing Technique to Monitor The Status of The Plant and Change Detection for Three Different Periods in Western Region in Baghdad/ Iraq - Najeeb, Ahmed (Iraqi Journal of Science, 2023)
Data of multispectral satellite image (Landsat- 5 and Landsat-7) was used to monitoring the case of study area in the agricultural (extension and plant density), using ArcGIS program by the method of analysis (Soil adjusted vegetative Index). The data covers the selected area at west of Baghdad Government with a part of the Anbar and Karbala Government. Satellite image taken during the years 1990, 2001 and 2007. The scene of Satellite Image is consists of seven of spectral band for each satellite, Landsat-5(TM) thematic mapper for the year 1990, as well as satellite Landsat-7 (ETM+) Enhancement thematic mapper for the year 2001 and 2007. The results showed that in the period from 1990 to 2001 decreased land area exposed (bare) and increased the space of land covered by vegetation in percentage (31.06%), while this was a slight increase in the period between 2001 to 2007 in percentage (17.22%).